Oxide Formation and Dissolution on Silicon in KOH Electrolyte: An In-Situ Infrared Study. Issue 5 (1st January 2016) - Philipsen, H. G. G.; Ozanam, F.; Allongue, P.; Kelly, J. J.; Chazalviel, J.-N.
Abstract : The n-Si(111)/6 M KOH electrolyte interface has been investigated by in-situ multiple-internal reflection infrared spectroscopy, at room temperature and at 40°C. The potential was stepped successively to positive and negative values with respect to open-circuit potential, during which surface oxidation and oxide dissolution occur, respectively. Infrared spectra were recorded together with the interfacial current. Analysis of the spectra indicates that formation of an oxide layer at the positive potential takes place in two steps: a first step associated with replacement of the surface SiH by SiOH or SiO − groups, and a second step, associated with the formation of SiOSi groups and growth of a passivating oxide layer. The mechanism is strongly dependent on the competition between oxidation and dissolution, which accounts for the complex shape of the current transient and its temperature dependence. At the negative potential, dissolution of the oxide takes place by random pitting, until the hydrogenated surface is restored.